One-pot preparation of dendrimer-gold nanoparticle hybrids in a dipolar aprotic solvent - Stemmler, Marco (Langmuir : the ACS journal of surfaces and colloids, 2009)
We present a simple one-pot, one-step method to obtain stable and nearly monodisperse gold nanoparticles in dipolar aprotic solvents. Novel thiomethyl-functionalized polyphenylene dendrimers are used to control the growth and stabilize the nanoparticles in suspension. The dendrimer functionalized gold nanoparticles have an average size of roughly 10 nm and are stable in suspension for several weeks. The stability in dipolar aprotic solvents and the great functionalization flexibility offered by the dendrimers make these metal/dendrimer hybrid systems promising for applications such as nanophotonics, molecular electronics, and sensing